ANALISIS TUTURAN IMPERATIF GURU DAN SISWA DI SMA NEGERI 5 PONTIANAK - Istiana, Istiana; Patriantoro, Patriantoro; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractImperative speech is found with a high level of frequency in everyday life Researchers choose imperative speech because imperative speech is used humans to communicate in everyday life. This research uses several methods, the first method for data collection is the method refer. Both methods of data analysis are descriptive method, context analysis, and comparative. The result of the analysis of imperative speech between teacher and student in SMA Negeri 5 Pontianak is that there is a form of speech imperative between teacher and student, meaning of imperative of teacher and student's speech, imperative pragmatic imperative in classroom learning between teacher and student. This study found the form of regular imperative sentences, sentence request, permission sentence, sentence solicitation, and imperative sentence. The meaning of the imperative pragmatic utterances found in this study is the meaning of command, order, request, insistence, madness, invitation, permission request, permit, prohibition and suggestion. Keywords: imperative speech, teacher, student